Cochlin Deficiency Protects Against Noise-Induced Hearing Loss - Seist, Richard; Landegger, Lukas D.; Robertson, Nahid G.; Vasilijic, Sasa; Morton, Cynthia C.; Stankovic, Konstantina M. (Frontiers in Molecular Neuroscience, 2021)
Cochlin is the most abundant protein in the inner ear. To study its function in response to noise trauma, we exposed adolescent wild-type (Coch+/+) and cochlin knock-out (Coch-/-) mice to noise (8-16 kHz, 103 dB SPL, 2h) that causes a permanent threshold shift and hair cell loss. Two weeks after noise exposure, Coch-/- mice had substantially less elevation in noise-induced auditory thresholds and hair cell loss than Coch+/+ mice, consistent with cochlin deficiency providing protection from noise trauma. Comparison of pre-noise exposure thresholds of auditory brain stem responses (ABRs) and distortion product otoacoustic emissions (DPOAEs) in Coch-/- mice and Coch+/+ littermates revealed a small and significant elevation in thresholds of Coch-/- mice, overall consistent with a small conductive hearing loss in Coch-/- mice. We show quantitatively that the pro-inflammatory component of cochlin, LCCL, is upregulated after noise exposure in perilymph of wild-type mice compared to unexposed mice, as well as the enzyme catalyzing LCCL release, aggrecanase1, encoded by Adamts4. We further show that upregulation of pro-inflammatory cytokines in perilymph and cochlear soft-tissue after noise exposure is lower in knock-out than wild-type mice. Taken together, our data demonstrate for the first time that cochlin deficiency results in conductive hearing loss that protects against physiologic and molecular effects of noise trauma.